Water Security: Water Management in Rural Communities of the Northern Pacific Region of Costa Rica - Serrano, Andrea Suárez (2019)
A group of 9 Associations for the Administration of Rural Aqueducts (ASADAS) located in the Northern Pacific region of Costa Rica were selected to evaluate their management and document the strategies they implemented during the drought of 2014-2016. Five basic management components were evaluated: administrative and financial, commercial, communal, water resources, and management of water systems, to determine if management was adequate to provide safe water to the communities. In addition, the quality of drinking water of each ASADA was analyzed, using Level 1 of the Regulation for Quality of Drinking Water (38924-S) as a criterion. One of the ASADAS studied had a high level of management capability; 3 had a low level of management capability, and 5 had weak management. The presence of fecal coliforms and E. coli was detected during the rainy season in 2 ASADAS. Only 3 of the 9 ASADAS analyzed met the optimal ranges for free residual chlorine, which endangers the quality of the water supplied to the population. It is concluded that the ASADAS evaluated are highly fragile when confronted by a hydrometeorological event, due to the age of systems, lack of maintenance, and the limited capacity of their storage tanks, which increases risk during extreme events (droughts and floods). In addition, the ASADAS evaluated had mostly low or weak management capabilities; consequently, the water that is distributed to communities could affect water security of the communities that they serve, since this water is not always available when needed and does not comply with some of the basic parameters of potability.